Src-family kinases negatively regulate NFAT signaling in resting human T cells - Baer, Alan (PLoS One, 2017)
T cell signaling is required for activation of both natural and therapeutic T cells including chimeric antigen receptor (CAR) T cells. Identification of novel factors and pathways regulating T cell signaling may aid in development of effective T cell therapies. In resting human T cells, the majority of Src-family of tyrosine kinases (SFKs) are inactive due to phosphorylation of a conserved carboxy-terminal tyrosine residue. Recently, a pool of enzymatically active SFKs has been identified in resting T cells; however, the significance of these is incompletely understood. Here, we characterized the role of active SFKs in resting human T cells. Pharmacologic inhibition of active SFKs enhanced distal TCR signaling as measured by IL-2 release and CD25 surface expression following TCR-independent activation. Mechanistically, inhibition of the active pool of SFKs induced nuclear translocation of NFAT1, and enhanced NFAT1-dependent signaling in resting T cells. The negative regulation of NFAT1 signaling was in part mediated by the Src-kinase Lck as human T cells lacking Lck had increased levels of nuclear NFAT1 and demonstrated enhanced NFAT1-dependent gene expression. Inhibition of active SFKs in resting primary human T cells also increased nuclear NFAT1 and enhanced NFAT1-dependent signaling. Finally, the calcineurin inhibitor FK506 and Cyclosporin A reversed the effect of SFKs inhibition on NFAT1. Together, these data identified a novel role of SFKs in preventing aberrant NFAT1 activation in resting T cells, and suggest that maintaining this pool of active SFKs in therapeutic T cells may increase the efficacy of T cell therapies.